Design And Performance Analysis of Mobile Data Networks: WLAN-Cellular Wan Interworking - Fredson, Alfred Phiri (2004)
This thesis presents a proposed design for interworking WLAN and cellular WAN technologies, with support for vertical handoffs. Specifically, the IEEE802.11b standard and the GPRS technologies are selected for the interworking design. The design is based on the tight coupling as opposed to the loose coupling architecture, proposed by the European Telecommunication Standards Institute(ETSI).